Investovanie do zlata s využitím reverzných bonusových sprint certifikátov - Harčariková, Monika (Univerzita Pardubice, 2016)
This paper performs an analysis of reverse bonus sprint certificate, the value of which is derived from an underlying asset. These certificates are designed with the aim to make a disproportionately higher profit in bear market. A replicating portfolio is created using option pricing formula for price the reverse bonus sprint certificate. Profit of the replicating portfolio is identical to profit from a combination of an underlying asset and financial derivative, i.e. vanilla and barrier option as it is proved in paper. Based upon a theoretical option pricing models, the replicating portfolio for reverse bonus sprint certificate in an analytical form on SPDR Gold Shares is engineered. There is created reverse bonus sprint certificate with various parameters and calculated the issue prices at the spot market. The profitability for potential investors at the expiration period are provided. Also, the relation between the investor´s profit change and parameters are detected. There are identified the best reverse bonus sprint certificate for every estimated development of the shares with the recommendation for investors. The main aim of the paper is to demonstrate the nature of the given certificate´s creation using option strategies with the increasing of the intellectualization of all potential investors.
Investing in Gold Using Reverse Bonus Sprint Certificates
Keywords: Reverse bonus sprint certificate; Replicating portfolio; Vanilla option; Barrier option; Option pricing; SPDR Gold Shares; G11; G13